Evolution of developmental and comparative immunology in poultry: The regulators and the regulated. (January 2023) - Lu, Mingmin; Lee, Youngsub; Lillehoj, Hyun S.
Abstract: Avian has a unique immune system that evolved in response to environmental pressures in all aspects of innate and adaptive immune responses, including localized and circulating lymphocytes, diversity of immunoglobulin repertoire, and various cytokines and chemokines. All of these attributes make birds an indispensable vertebrate model for studying the fundamental immunological concepts and comparative immunology. However, research on the immune system in birds lags far behind that of humans, mice, and other agricultural animal species, and limited immune tools have hindered the adequate application of birds as disease models for mammalian systems. An in-depth understanding of the avian immune system relies on the detailed studies of various regulated and regulatory mediators, such as cell surface antigens, cytokines, and chemokines. Here, we review current knowledge centered on the roles of avian cell surface antigens, cytokines, chemokines, and beyond. Moreover, we provide an update on recent progress in this rapidly developing field of study with respect to the availability of immune reagents that will facilitate the study of regulatory and regulated components of poultry immunity. The new information on avian immunity and available immune tools will benefit avian researchers and evolutionary biologists in conducting fundamental and applied research. Highlights: Avian has a unique immune system compared to its mammalian counterparts. The understanding of the avian immune component repertoire is limited but still expanding. We review current knowledge on avian cell surface markers, cytokines, chemokines, and beyond. Recent progress on immune reagents for these regulatory and regulated components is updated. The new information on avian immunity and immune tools benefits fundamental and applied studies.